Speciation and historical invasions of the Asian black-spined toad (Duttaphrynus melanostictus) - Christophe Dufresnes; Daniel Jablonski; Johanna Ambu; Vishal Kumar Prasad; Kumudani Bala Gautam; Rachunliu G. Kamei; Stephen Mahony; Sylvia Hofmann; Rafaqat Masroor; Bérénice Alard; Angelica Crottini; Devin Edmonds; et al. (Nature Communications)
Abstract Animal translocations provide striking examples of the human footprint on biodiversity. Combining continental-wide genomic and DNA-barcoding analyses, we reconstructed the historical biogeography of the Asian black-spined toad (Duttaphrynus melanostictus), a toxic commensal amphibian that currently threatens two biodiversity hotspots through biological invasions (Wallacea and Madagascar). The results emphasize a complex diversification shaped by speciation and mitochondrial introgression that comprises two distinct species. One species (true D. melanostictus) is distributed in the Indian subcontinent and is invasive in Wallacea. The other species, whose nomenclature remains unsettled, diverged from D. melanostictus in the Miocene era (~7 Mya) and diversified across Southeast Asia, from where it was introduced to Madagascar. Remarkably, the Indonesian population of D. melanostictus was recently established from India, which suggests historical, possibly human-assisted dispersal across the Bay of Bengal, reflecting the centuries-old connection between these regions.